2018
DOI: 10.4314/tjpr.v17i4.5
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene alleviates bone cancer-related pain in rats by modulating N-methyl-D-aspartate receptor 2B subunit

Abstract: Purpose: To investigate the effect of β-elemene on bone cancer-related pain (BCRP) and its underlying mechanism in a rat model. Methods: A rat model of BCRP was established by injection of Walker 256 cells into the medullary cavity in adult male Sprague-Dawley rats. The effects of β-elemene on pain-related behaviours were assessed by paw withdrawal mechanical threshold (PWMT) and paw withdrawal thermal latency (PWTL). Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…For example, β -Elemene induces apoptosis in ovarian cancer cells by activating the STAT-NF- κ B pathway [ 16 ]. Moreover, the available literature demonstrates that β -Elemene has been proved to alleviate bone cancer pain in rats by regulating the N-methyl-D-aspartate receptor 2B subunit (NR2B) [ 17 ], which plays a key role in the progression of MT [ 18 ]. However, the role of β -Elemene in MT of bone cancer pain has not been clarified and needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, β -Elemene induces apoptosis in ovarian cancer cells by activating the STAT-NF- κ B pathway [ 16 ]. Moreover, the available literature demonstrates that β -Elemene has been proved to alleviate bone cancer pain in rats by regulating the N-methyl-D-aspartate receptor 2B subunit (NR2B) [ 17 ], which plays a key role in the progression of MT [ 18 ]. However, the role of β -Elemene in MT of bone cancer pain has not been clarified and needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Gong LY et al reported that β-elemene could alleviate cancer pain by downregulating spinal NR2B expression. 69 In light of these findings, we propose that β-elemene may indirectly inhibit spinal sensitization by inhibiting astrocyte-related inflammatory processes. As mentioned before, spinal neural activation precedes that of microglia and astrocytes.…”
Section: Discussionmentioning
confidence: 90%
“…In the last 10 years, with the technological developments in cancer diagnosis and therapy, the rates of survivors with cancer are increasing The issue of making certain how to improve the life quality of patients with cancer has aggregated a number of common concerns. In terms of an effective method to relieve cancer pain, Gong et al 42 demonstrated that 3-elemene has an ideal effect in relieving pain behavior in a rat model of BCRP.…”
Section: Discussionmentioning
confidence: 99%